2007
DOI: 10.1029/2006jd007347
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the intraseasonal variability of tropospheric ozone over the Indian Ocean during the winter monsoon

Abstract: [1] We synthesize daily sonde (vertical) information and daily satellite (horizontal) information to provide an empirical description of ozone origins over the northern Indian Ocean during the INDOEX (Indian Ocean Experiment) field campaign (February-March 1999). This area is shown to be a significant portion of the ''high-ozone tropics''. East-west O 3 features and their flow are identified, and ozone origins are compared to other tropical regions, using water vapor as a second tracer. In the study period, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…-frequently observed free tropospheric layers, usually between 5 and 10 km, with elevated mixing ratios of O 3 and other pollutants; these were originally primarily attributed to long-range transport of polluted air masses from biomass burning in African , although a recent, more detailed analysis (Chatfield et al, 2007) has shown that primary contributions come from stratospheric input of O 3 and from convective lofting of pollutants out of the polluted MBL of the northern Indian Ocean;…”
Section: Outflow Channels and Layersmentioning
confidence: 99%
See 3 more Smart Citations
“…-frequently observed free tropospheric layers, usually between 5 and 10 km, with elevated mixing ratios of O 3 and other pollutants; these were originally primarily attributed to long-range transport of polluted air masses from biomass burning in African , although a recent, more detailed analysis (Chatfield et al, 2007) has shown that primary contributions come from stratospheric input of O 3 and from convective lofting of pollutants out of the polluted MBL of the northern Indian Ocean;…”
Section: Outflow Channels and Layersmentioning
confidence: 99%
“…However, two particular criticisms of de Laat (2002) were raised by Mandal (2002): the assumption of an African BMB source is not consistent with the dataset south of the ITCZ, where similar ozone layers were encountered in the UT, but no biomass burning source should be available from Africa (i.e., stratospheric injection must be playing a significant role there); and only a subset (about half) of the available ozone soundings were selected for the analysis, possibly missing important signals in the remaining data. Chatfield et al (2007) also state that though some of their trajectories do originate from the region west of North Africa, none come "close to either lightning or the potential venting of biomass burning." Sorting out this disagreement definitively will make an interesting future topic of research in this area of the field.…”
Section: Origins Of the Saw-abcmentioning
confidence: 99%
See 2 more Smart Citations
“…De Laat, 2002;Chatfield et al, 2007;Lawrence and Lelieveld, 2010). In particular, O 3 peaks reaching 120 ppbv were often found in the UT within layers 1Á2 km thick just below the tropopause (De Laat et al, 1999).…”
Section: Introductionmentioning
confidence: 99%